Current trends and research advances on the application of TiO2 nanoparticles in dentistry: How far are we from clinical translation? - Hossein Mohammadi; Hedaiat Moradpoor; Salmia Beddu; Hamid Reza Mozaffari; Roohollah Sharifi; Razieh Rezaei; Nima Fallahnia; Mona Ebadi; Saiful Amri Mazlan; Mohsen Safaei (Heliyon)
The great potential of nanotechnology-based knowledge during the past decade has shown great potential to elevate human living standards and enhance healthcare conditions through diagnosing, preventing, and treating different diseases. Among abundant nanoparticles (NPs), inorganic NPs feature distinctive biological and physicochemical properties compared to their conventional counterparts which do not endow. TiO2 NPs possess excellent properties including low-cast, antibacterial properties, biocompatibility, and physicochemical stability. The present review highlights and discusses the current trends in applying TiO2 NPs in dentistry ranging from TiO2-based nanocomposite in endodontics, orthodontics, and biofilm prevention. Moreover, the potential of TiO2 NPs in developing new photodynamic therapy and the next generation of oral care products is outlined. In the end, the clinical translation of TiO2-based dental materials is brought to the forefront which is impetus and of great importance to developing inorganic NP-based dental materials.